Analysis of the Quality of Health Services on Outpatient Satisfaction at the Outpatient Clinic of Kolodale Regional Hospital, North Morowali Regency, Indonesia - Harniati; Basri, Mohammad; Syakur, Rosdiana; Pakingki, Oktavianus (Postgraduate, University of Mataram, 2023)
Health services have an important role in the implementation of health services in hospitals as a whole, especially nursing. Health services are considered good if the health services can create a feeling of satisfaction for each patient. Achieving a level of satisfaction with the services provided to patients, both the quality of health services and the health service system, means that patients will prefer quality health services that are quality, guaranteed, and affordable to patients, or in other words, consumers are one of the most important factors in achieving the level of satisfaction in a health service. This research aims to analyze the quality of health services on the satisfaction of outpatients at Kolonodale Hospital, North Morowali Regency. This research is a quantitative study that uses an analytical survey research method with a